OP256 Recognising The Broader Value Of Vaccines In Health Technology Assessment: Worth A Shot?. (December 2021) - Neri, Margherita; Brassel, Simon; Steuten, Lotte
Abstract : Introduction: The COVID-19 pandemic shows that the impact of effective vaccines extends well beyond vaccinated individuals and healthcare systems. Yet, these externalities are not typically considered in health technology assessments (HTA) which may underestimate vaccines' broader value. We explored to what extent future vaccines relevant to England might exhibit such broader value. Methods: We compared the ten value elements of an existing vaccine evaluation framework to the value elements considered in England according to the Joint Committee on Vaccine and Immunisation (JCVI) and the National Institute for Health and Care Excellence's (NICE) guidelines. Using literature and expert opinion we then explored, for a selection of ten vaccines with an expected UK-launch within five years, on which value elements each vaccine might potentially show added value. Results: Up to five of ten value elements are unlikely to be considered by JCVI or NICE, including patient and carer productivity, enablement value, impact on antimicrobial resistance and transmission value. Of vaccines studied, 100 percent will potentially generate value on at least one broader value element that is currently ignored; 60 percent to 80 percent may increase vaccinee/patient or carer productivity respectively. Conclusions: There is a substantial gap between value generation and value recognition of vaccines in HTA in England. This might lead to undervaluation and underutilization of vaccines, leaving societies more vulnerable than needed when faced with infectious diseases.